Experimental evidence of a change of exchange anisotropy sign with temperature in Zn-substituted Cu_{2}OSeO_{3} - S. H. Moody; P. Nielsen; M. N. Wilson; D. Alba Venero; A. Štefančič; G. Balakrishnan; P. D. Hatton (Physical Review Research, 2021)
We report small-angle neutron scattering from the conical state in a single crystal of Zn-substituted Cu_{2}OSeO_{3}. Using a 3D vector-field magnet to reorient the conical wave vector, our measurements show that the magnitude of the conical wave vector changes as a function of crystallographic direction. These changes are explained using the anisotropic exchange interaction (AEI) within the continuum model, whose magnitude in free-energy transitions from a maxima to a minima along the 〈111〉 and 〈100〉 crystallographic directions respectively. We further find that the AEI free-energy constant undergoes a change of sign from positive to negative with decreasing temperature. Unlike in the related compound FeGe, where similar behavior of the AEI induces a reorientation of the helical wave vector, we show that the zero field helical wave vector in (Cu_{0.98}Zn_{0.02})_{2}OSeO_{3} remains along the 〈100〉 directions at all temperatures due to the competing fourth-order magnetocrystalline anisotropy becoming dominant at lower temperatures.